Excitons in bulk black phosphorus evidenced by photoluminescence at low temperature. (6th January 2021) - Carré, E; Sponza, L; Lusson, A; Stenger, I; Gaufrès, E; Loiseau, A; Barjon, J
Abstract: Atomic layers of black phosphorus (BP) present unique opto-electronic properties dominated by a direct tunable bandgap in a wide spectral range from visible to mid-infrared (IR). In this work, we investigate the IR photoluminescence (PL) of BP single crystals at very low temperature. Near-band-edge recombinations are observed at 2 K, including dominant excitonic transitions at 0.276 eV and a weaker one at 0.278 eV. The free-exciton binding energy is calculated with an anisotropic Wannier–Mott model and found equal to 9.1 meV. On the contrary, the PL intensity quenching of the 0.276 eV peak at high temperature is found with a much smaller activation energy, attributed to the localization of free excitons on a shallow impurity. This analysis leads us to attribute respectively the 0.276 eV and 0.278 eV PL lines to bound excitons and free excitons in BP. As a result, the value of bulk BP bandgap is refined to 0.287 eV at 2 K.